The utility of handheld metal detector in confirming metallic foreign body ingestion in the pediatric emergency department - Eylem Ulaş SAZ; Çiğdem ARIKAN; Funda ÖZGENÇ; Muhterem DUYU; Yeliz OZANANAR (Turkish Journal of Gastroenterology, 2019)
-